Dynamics of Nucleosomal Structures Measured by High-Speed Atomic Force Microscopy - Katan, Allard J.; Vlijm, Rifka; Lusser, Alexandra; Dekker, Cees (Small (Weinheim an der Bergstrasse, Germany), 2015)
The accessibility of DNA is determined by the number, position, and stability of nucleosomes, complexes consisting of a core of 8 histone proteins with DNA wrapped around it. Since the structure and dynamics of nucleosomes affects essential cellular processes, they are the subject of many current studies. Here, high‐speed atomic force microscopy is used to visualize dynamic processes in nucleosomes and tetrasomes (subnucleosomal structures that contain 4 rather than 8 histones in the protein core). Nucleosomes can spontaneously disassemble in a process (at a 1 second timescale). For tetrasomes, multiple dynamic phenomena are observed. For example, during disassembly the formation of a DNA loop (∼25 nm in length) is seen, which remains stable for several minutes. For intact tetrasomes, dynamics in the form of sliding and reversible hopping between stable positions along the DNA are observed. The data emphasize that tetrasomes are not merely static objects but highly dynamic. Since tetrasomes (in contrast to nucleosomes) can stay on the DNA during transcription, the observed tetrasome dynamics is relevant for an understanding of the nucleosomal dynamics during transcription. These results illustrate the diversity of nucleosome dynamics and demonstrate the ability of high speed AFM to characterize protein‐DNA interactions. Tetrasomes and nucleosomes assembled by NAP1 are imaged at subsecond timescales with atomic force microscopy. Several different pathways of disassembly are found and the spontaneous transition between two rotational states of tetrasomes is confirmed by direct imaging.